Technical analysis of the currency market : - Schlossberg, Boris (John Wiley & Son, 2006)
This dynamic and all-inclusive FX trading primer provides you with a practical, market-proven arsenal of currency trading weapons and solid tactical knowledge. From a focused look at how the FX market works to specific trading setups designed to produce high-probability profits in the widest possible range of market situations, Technical Analysis of the Currency Market explores: Important similarities and differences between the FX market and equity, option, and other financial markets; Five key themes that drive the currency markets and which technical tools traders can use to best exploit them; Technical analysis insights and examples for both trend and range trading setups; Five chart patterns, well known to equity analysts, that have proven effective in currency trading; Oscillator strategies for spotting quickly developing divergences between momentum and price; Methods for spotting common price patterns that are the building blocks for understanding and interpreting price flow.